Influence of ion implantation on mechanical properties of U8А steel and cobalt-tungsten carbide plates; Energy Fluxes and Radiation Effects (EFRE-2016) - Rechenko D. Denis; Popov A. Andrey; Gricenko (Gritsenko) B. P. Boris Petrovich; Sungatulin A. Alfred; Sergeev V. P. Viktor Petrovich; Kalashnikov M. P. Mark Petrovich (2016, 2016)
Title screen